Maternal use of probiotics during pregnancy and effects on their offspring’s health in an unselected population - Rutten, Nicole (Eur J Pediatr, 2015)
Probiotics are used by women in the perinatal period and may improve balance of microbiota, with possible health benefits for both mother and baby. Characteristics and (health) behaviour patterns of mothers using probiotics during pregnancy, and health effects on their offspring, were investigated. Differences between mothers using probiotics during pregnancy and those who did not, were assessed. In total, 341 out of 2491 (13.7 %) mothers reported use of probiotics during pregnancy. There were no significant differences in maternal features (gestation, age, ethnicity, education) between users and non-users. Logistic regression analyses showed that consumption of probiotics was significantly associated with use of homeopathic products [odds ratio (OR) 1.65, 95 % confidence interval (CI) 1.17–2.33, p = 0.005], maternal history of smoking (OR 1.72, 95 % CI 1.25–2.37, p = 0.001) and paternal history of smoking (OR 1.39, 95 % CI 1.01–1.89, p = 0.05). Common disease symptoms during the first year of life in the offspring did not differ between both groups. Conclusion: The use of probiotics or other health-related products without doctor’s prescription during pregnancy might point to compensation for types of less favourable behaviour. Probiotic use during pregnancy does not seem to induce positive health effects in the offspring in an unselected population.